2016
DOI: 10.1016/j.abb.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epicatechin improves insulin sensitivity in high fat diet-fed mice

Abstract: Obesity constitutes a major public health concern, being frequently associated with type 2 diabetes (T2D). Evidence from studies in humans and experimental animals suggest that consumption of the flavan-3-ol (−)-epicatechin (EC) and of EC-rich foods may improve insulin sensitivity. To further understand the potential benefits of dietary EC consumption on insulin resistance, this study investigated the capacity of EC supplementation to prevent high fat diet (HFD)-induced insulin resistance in mice. To assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 42 publications
5
80
0
1
Order By: Relevance
“…We previously demonstrated that EC supplementation can protect rats from insulin resistance by high fructose consumption (Bettaieb et al, 2014) and by the consumption of a HFD in mice (Cremonini et al, 2016). In both conditions EC caused a major improvement in adipose tissue insulin sensitivity which was affected by chronic consumption of excess energy (as fructose or fat).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that EC supplementation can protect rats from insulin resistance by high fructose consumption (Bettaieb et al, 2014) and by the consumption of a HFD in mice (Cremonini et al, 2016). In both conditions EC caused a major improvement in adipose tissue insulin sensitivity which was affected by chronic consumption of excess energy (as fructose or fat).…”
Section: Introductionmentioning
confidence: 99%
“…EC supplementation mitigates systemic and adipose tissue insulin resistance in a mouse model of HFD-induced obesity and insulin resistance (Cremonini et al, 2016). In this study, we investigated whether improved insulin sensitivity caused by EC supplementation could be in part caused by EC capacity to inhibit adipose tissue inflammation, ER and oxidative stresses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent studies have shown antiinflammatory and antioxidant effects of PB2 and EPC, which exert positive effects by improving diabetes comorbidities. They were observed to bring improvement in insulin sensitivity and to exert a protective effect against diabetic nephropathy and cardiomyopathy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Epicatechin is present in high concentrations in many plant foods, especially in fruits. Many healthy effects of epicatechin have been reported previously, including improving insulin sensitivity, [22] anti-allergy, [23] retarding Alzheimer's disease, [24] etc. Epicatechin was detected in all 15 determined Bulgarian fruits, [25] except melon.…”
Section: Phenolic Compositionsmentioning
confidence: 99%